2015
DOI: 10.1039/c4ra15382k
|View full text |Cite
|
Sign up to set email alerts
|

Copper nanoparticles as an efflux pump inhibitor to tackle drug resistant bacteria

Abstract: Casein capped copper nanoparticles at sub inhibitory concentrations function as an efflux pump inhibitor and restores susceptibility to antibiotics in drug resistant bacteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
51
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(55 citation statements)
references
References 73 publications
0
51
0
Order By: Relevance
“…To move noxious agents from the inside out, the efflux pump utilizes energy sources through proton motive force (PMF) or ATP synthesis (25). Thus, one possibility for rationalizing the loss of efflux pump activity is that intracellular ATP is depleted due to the inhibition of ATPase by ROS (19,26). This is also associated with the abortion of DNA replication, resulting in no bacterial growth (26).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To move noxious agents from the inside out, the efflux pump utilizes energy sources through proton motive force (PMF) or ATP synthesis (25). Thus, one possibility for rationalizing the loss of efflux pump activity is that intracellular ATP is depleted due to the inhibition of ATPase by ROS (19,26). This is also associated with the abortion of DNA replication, resulting in no bacterial growth (26).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, one possibility for rationalizing the loss of efflux pump activity is that intracellular ATP is depleted due to the inhibition of ATPase by ROS (19,26). This is also associated with the abortion of DNA replication, resulting in no bacterial growth (26). A previous study conducted by Berney,Weilenmann,and Egli (19) demonstrated that UV-A light rapidly diminished ATP and simultaneously inactivated efflux pump activity.…”
Section: Discussionmentioning
confidence: 99%
“…Inspite of their bioactivity, the antibiofilm potential of CuNPs is rarely explored [17]. Only a few reports are published in the last year on, the use of copper-containing nanoparticles in the treatment of biofilms [9,18].…”
Section: Introductionmentioning
confidence: 99%
“…Treatment of P. aeruginosa with CuNPs displayed cell death while S. aureus showed loss of colony formation which may be the cause of cell death(fig 3). Thus, it clear that CuNPs act as potent efflux pump inhibitors and also caused cell death by damaging the cell membrane which is similar to the mode of action of antibiotics(Christena et al,2015).5.3. Inhibition of enzyme by nanoparticlesEnzymesare one of the major bacterial virulence factors during infection caused by the bacteria.…”
mentioning
confidence: 80%